Transplacental transfer of RSV antibody in Australian First Nations infants. Issue 2 (16th October 2021) - Homaira, Nusrat; Binks, Michael; Walker, Gregory; Larter, Natasha; Clark, Katrina; Campbell, Megan; McHugh, Lisa; Briggs, Nancy; Nyiro, Joyce; Stelzer‐Braid, Sacha; Hu, Nan; Macartney, Kristine; et al.
Abstract: Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory infection hospitalisations in Aboriginal infants specifically those aged <6 months. Maternally derived RSV antibody (Ab) can protect against severe RSV disease in infancy. However, the efficiency of transplacental transfer of maternal anti‐RSV Ab remains unknown in Aboriginal infants. We characterised RSV Ab in Australian First Nations mother‐infant pairs ( n  = 78). We investigated impact of covariates including low birthweight, gestational age (GA), sex of the baby, maternal age and multiparity of the mother on cord to maternal anti‐RSV Ab titre ratio (CMTR) using multivariable logistic regression model. All ( n  = 78) but one infant was born full term (median GA: 39 weeks, interquartile range: 38–40 weeks) and 56% were males. The mean log2 RSV Ab titre was 10.7 ( SD ± 1.3) in maternal serum and 11.0 ( SD  ± 1.3) in cord serum at birth; a ratio of 1.02 ( SD  ± 0.06). One‐third of the pairs had a CMTR of <1 indicating impaired transfer. Almost 9% (7/78) of the term infants had cord RSV Ab levels below 2 9. Covariates showed no effect on CMTR. Further mechanistic research is needed to determine the significance of these findings on RSV disease in First Nations children.